Spatial Separation of Litter Decomposition and Mycorrhizal Nitrogen Uptake in a Boreal Forest - Lindahl, Björn D.; Katarina Ihrmark; Johanna Boberg; Trumbore, Susan E.; Högberg, Peter; Stenlid, Jan; Finlay, Roger D. (The New phytologist, 2007)
$\bullet$Our understanding of how saprotrophic and mycorrhizal fungi interact to recirculate carbon and nutrients from plant litter and soil organic matter is limited by poor understanding of their spatiotemporal dynamics.$\bullet$In order to investigate how different functional groups of fungi contribute to carbon and nitrogen cycling at different stages of decomposition, we studied changes in fungal community composition along vertical profiles through a Pinus sylvestris forest soil. We combined molecular identification methods with14C dating of the organic matter, analyses of carbon:nitrogen (C:N) ratios and15N natural abundance measurements.$\bullet$Saprotrophic fungi were primarily confined to relatively recently (< 4 yr) shed litter components on the surface of the forest floor, where organic carbon was mineralized while nitrogen was retained. Mycorrhizal fungi dominated in the underlying, more decomposed litter and humus, where they apparently mobilized N and made it available to their host plants.$\bullet$Our observations show that the degrading and nutrient-mobilizing components of the fungal community are spatially separated. This has important implications for biogeochemical studies of boreal forest ecosystems.